Improving Labor Safety at Cotton Ginning Enterprises - Tukhtabaev, S. T.; Mukimov, N. B. (European Journal of Life Safety and Stability (2660-9630), 2022)
This article describes the labor activity of employees in the enterprises of the cluster system, indicators of negative factors affecting the work process and ways to eliminate them, the inadequacy of the personal clothing used, and the need to combat the resulting obstruction of work.